2011
DOI: 10.3892/ijmm.2011.854
|View full text |Cite
|
Sign up to set email alerts
|

A sulfated polysaccharide, fucoidan, enhances the immunomodulatory effects of lactic acid bacteria

Abstract: Abstract. Fucoidan, a sulfated polysaccharide contained in brown algae, has a variety of immunomodulatory effects, including antitumor and antiviral effects. On the other hand, lactic acid bacteria (LAB) also have immunomodulatory effects such as anti-allergic effects. In this study, we demonstrated that fucoidan enhances the probiotic effects of LAB on immune functions. By using Peyer's patch cells and spleen cells in vitro, fucoidan amplified interferon (IFN)-γ production in response to a strain of LAB, Tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
(62 reference statements)
2
15
0
1
Order By: Relevance
“…Recently, the genetic diversity of Tetragenococcus in some salt‐ and sugar‐rich environments has been determined by PCR‐based molecular approaches, yet still only a limited number of species have been isolated (Juste and others ; Fukui and others ; Nam and others ; Chuon and others ). It was recently reported that T. halophilus has an immunomodulatory effect that attenuates allergic symptoms by promoting Th1/Th2 immune balance (Masuda and others ; Kawashima and others ). However, further studies will be needed in order to fully understand the characteristics of this genus.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the genetic diversity of Tetragenococcus in some salt‐ and sugar‐rich environments has been determined by PCR‐based molecular approaches, yet still only a limited number of species have been isolated (Juste and others ; Fukui and others ; Nam and others ; Chuon and others ). It was recently reported that T. halophilus has an immunomodulatory effect that attenuates allergic symptoms by promoting Th1/Th2 immune balance (Masuda and others ; Kawashima and others ). However, further studies will be needed in order to fully understand the characteristics of this genus.…”
Section: Resultsmentioning
confidence: 99%
“…Alginic acid, an anionic polysaccharide in Sargassum wightii , exhibited anti-inflammatory effects in a rat study of adjuvant-induced arthritis [80]. Fucoidan is known to enhance the probiotic effects of Lactic acid bacteria (LAB) by immunomodulation of an anti-allergic response [81]. Fucans from Lobophora variegata [82], Sargassum vulgare [83], and Spatoglossum schroederi [84] also have both anti-inflammatory and antinociceptive effects.…”
Section: Anti-inflammatory and Antinociceptive Properties Of Marine Amentioning
confidence: 99%
“…These effects promote the activation of natural killer (NK) cells, resulting in enhancement of pro-inflammatory cytokine production and anti-viral action [18]. Moreover, fucoidan can potently induce production of interferon-γ (IFN-γ) by CD4 and CD8 T cells and induce T cell cytotoxicity against antigen-expressing human cancer cells or bacteria [19], [20]. In addition, fucoidan has been shown to induce activation and maturation of human and mouse DCs in vitro [21][23].…”
Section: Introductionmentioning
confidence: 99%